Public Security in the Negotiated State - Müller, Markus-Michael. author. aut Link
XII, 269 p.
Keywords: Policing and security governance in areas of limited statehood have become central issues in contemporary academic and political debates. This book offers an in-depth study on public security provision, the resulting state-society relations, and policing in Mexico City.